The hitchhiker's guide to missing import price changes and pass-through - Etienne Gagnon; Benjamin R. Mandel; Robert J. Vigfusson (Federal Reserve Bank of New York, 2012)
A large body of empirical work has found that exchange rate movements have only modest effects on inflation. However, the response of an import price index to exchange rate movements may be underestimated because some import price changes are missed when constructing the index. We investigate downward biases that arise when items experiencing a price change are especially likely to exit or to enter the index. We show that, in theoretical pricing models, entry and exit have different implications for the timing and size of these biases. Using Bureau of Labor Statistics microdata, we derive empirical bounds on the magnitude of these biases and construct alternative price indexes that are less subject to selection effects. Our analysis suggests that the biases induced by selective exits and entries do not materially alter the literature's view that pass-through to U.S. import prices is low over the short- to medium-term horizons that are most useful for both forecasting and differentiating among economic models.
Keywords: F31; F41; E30; E01; C81; 330; exchange rate pass-through; price index; Exchange Rate Pass-Through; Außenhandelspreis; Inflation; Außenhandelspreisindex; Lebenshaltungsindex; USA